Actin-depolymerizing Factor and Cofilin-1 Play Overlapping Roles in Promoting Rapid F-Actin Depolymerization in Mammalian Nonmuscle Cells - Hotulainen, Pirta (The American Society for Cell Biology, 2005)
Actin-depolymerizing factor (ADF)/cofilins are small actin-binding proteins found in all eukaryotes. In vitro, ADF/cofilins promote actin dynamics by depolymerizing and severing actin filaments. However, whether ADF/cofilins contribute to actin dynamics in cells by disassembling “old” actin filaments or by promoting actin filament assembly through their severing activity is a matter of controversy. Analysis of mammalian ADF/cofilins is further complicated by the presence of multiple isoforms, which may contribute to actin dynamics by different mechanisms. We show that two isoforms, ADF and cofilin-1, are expressed in mouse NIH 3T3, B16F1, and Neuro 2A cells. Depleting cofilin-1 and/or ADF by siRNA leads to an accumulation of F-actin and to an increase in cell size. Cofilin-1 and ADF seem to play overlapping roles in cells, because the knockdown phenotype of either protein could be rescued by overexpression of the other one. Cofilin-1 and ADF knockdown cells also had defects in cell motility and cytokinesis, and these defects were most pronounced when both ADF and cofilin-1 were depleted. Fluorescence recovery after photobleaching analysis and studies with an actin monomer-sequestering drug, latrunculin-A, demonstrated that these phenotypes arose from diminished actin filament depolymerization rates. These data suggest that mammalian ADF and cofilin-1 promote cytoskeletal dynamics by depolymerizing actin filaments and that this activity is critical for several processes such as cytokinesis and cell motility.